Teorema de Pitágoras: aplicações em objetos de aprendizagem - Balbino Júnior, Valci Rodrigues [UNESP] (2015)
This research studies the famous Pythagorean theorem, including some demonstrations, applications and the development of a learning object. The main purpose of this learning object is to help students from basic education with the geometric comprehension of the theorem in a ludic way. The part of the theory of the angles geometry necessary to the understanding of this study will be presented, so the demonstrations can be better understood. This work will be divided in four parts: A brief history; Geometric Concepts; Pythagorean Theorem; Learning Objects. A brief history presents the philosophical, cultural and historical aspects that in uenced many civilizations as a result of the theorem. Geometric Concepts is about the properties and the basic concepts of the geometry, especially the triangle geometry, which is essential to the development unleashed by the theory. Pythagorean Theorem presents demonstrations and results of the theorem or that are resulting from it. Learning Object covers the theoretical and practical aspects in the development of a learning object created in Flash